Investigation of Doppler Frequency Shift Effect on the Performance of Four-Channel Space Chaotic Laser Communication - Mi Li; Xue Wang; Yisi Wang; You Guo; Jisun Chen; Yijun Jiang (IEEE Photonics Journal)
In this article, the wavelength division multiplexing (WDM) technology is applied to the space chaotic laser communication system. We deduce the bit error rate (BER) model of multi-channel space chaotic laser communication with Doppler frequency shift. Based on the BER model, the effect of Doppler frequency shift on the performance of four-channel space chaotic laser communication systems on the synchronous orbit(GEO)-low earth orbit(LEO) and GEO-mid earth orbit(MEO) has been discussed in detail. The numerical simulation results indicate that the effect of Doppler frequency shift on GEO-LEO system is much less than GEO-MEO system. Therefore, the Doppler frequency shift effect of GEO-LEO system can be overcome by redundant design, and the Doppler frequency shift effect of GEO-MEO system must be paid more attention to the optimum design. Besides, the relationship between the performance of communication system and frequency shift under different channels are similar. The result has an important implication for reducing the complexity of the system design. These results of the article are significant for the design of the four-channel space chaotic laser communication system.